2017
DOI: 10.1080/15459624.2016.1250004
|View full text |Cite
|
Sign up to set email alerts
|

Wildland firefighter deaths in the United States: A comparison of existing surveillance systems

Abstract: Wildland fire fighting is a high-risk occupation requiring considerable physical and psychological demands. Multiple agencies publish fatality summaries for wildland firefighters; however, the reported number and types vary. At least five different surveillance systems capture deaths, each with varying case definitions and case inclusion/exclusion criteria. Four are population-level systems and one is case-based. System differences create challenges to accurately characterize fatalities. Data within each of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…The extraction form was developed based on the Cochrane Collaboration's data collection form [17], amended to contain fields relevant to this review. The data extracted included the authors' names, year of publication, article title, study design, brief description of the study, location, setting (e.g., prescribed ministration [9] as well as physical and mental health hazards [10]. A risk assessment accounting for daily exposure, the annual number of working days, and career length suggests that exposures to benzene, formaldehyde, acrolein, and particulate matter are sufficient to pose health concerns [4].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…The extraction form was developed based on the Cochrane Collaboration's data collection form [17], amended to contain fields relevant to this review. The data extracted included the authors' names, year of publication, article title, study design, brief description of the study, location, setting (e.g., prescribed ministration [9] as well as physical and mental health hazards [10]. A risk assessment accounting for daily exposure, the annual number of working days, and career length suggests that exposures to benzene, formaldehyde, acrolein, and particulate matter are sufficient to pose health concerns [4].…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Several US-based systems currently store and disseminate information on wildland fire-related injuries and fatalities. Butler et al (2017) reviewed five different surveillance systems that are used to report wildland firefighter fatalities, which include systems maintained by the US Fire Administration, the National Fire Protection Association, the US Bureau of Labour Statistics, National Institute for Occupational Safety and Health and the National Wildfire Coordinating Group. Butler et al (2017) found that there was substantial overlap among the systems, with each having a slightly different focus based on criteria formally required by law and how each system deals with unique subsets of wildland firefighter tasks and duties (e.g.…”
Section: Report Archiving and Accessmentioning
confidence: 99%
“…Either by law or practice, many of the systems store data related to the same incident, resulting in duplication, which is both inefficient and potentially confusing. As noted by Butler et al (2017), some systems are required to track firefighter fatalities owing to various legal statutes, whereas others may not include fatalities associated with some specific tasks and duties. Having multiple reporting systems with different inclusion criteria makes it difficult to assess the quality and completeness of the datasets.…”
Section: Current Limitationsmentioning
confidence: 99%
“…Over the past 30 years, area burned has doubled while suppression spending tripled [3]. Suppression costs are not only monetary: Suppression has altered the distribution of vegetation and wildlife, exacerbated fire hazards [4,5], and killed dozens of wildfire fighters in Canada [6] and the United States [7]. However, it is not clear how much suppression activities reduce wildfire likelihood to communities or other highly-valued resources and assets.…”
Section: Introductionmentioning
confidence: 99%